Tar spot disease of sorghum plants caused by Phyllachora sp. in Bogor, Gunung Kidul and West Lombok, Indonesia - Astuti, Dwi; Wiyono, Suryo; Hidayat, Sri Hendrastuti; Trikoesoemaningtyas, Trikoesoemaningtyas; Nugroho, Satya (Universitas Lampung, 2023)
The sorghum (Sorghum bicolor) plant is highly tolerant and adapted to drought. It has the potential to be developed and planted on marginal land in Indonesia. Tar spot disease is one of the obstacles to sorghum cultivation. In Indonesia, there is no report yet about this disease, especially on sorghum. To achieve optimal disease management, information on disease incidence and severity levels, as well as pathogen tar spot disease identification, are required. The aims of this study were to morphologically identify the pathogen and determine the level of incidence and severity of tar spot in sorghum cultivation areas in Bogor Regency, Gunung Kidul Regency, and West Lombok Regency. The disease observations were carried out on 17 sorghum varieties from the three areas with no experimental design. The results of the observation of the tar spot disease incidence in 17 varieties of sorghum from Bogor, Gunung Kidul, and West Lombok were 100%. The level of tar spot disease severity varied from 32.4% in the Latu Keta sorghum variety to the highest of 87.9% in the Samurai sorghum variety. The macroscopic and microscopic observation results of tar spot on sorghum plants showed that the cause of the tar spot disease was the Phyllachora fungi. This is the first report of a tar spot on sorghum caused by Phyllachora sp. in Indonesia.